Nanoencapsulated Mentha pulegium essential oil enhances the preservation of meat quality - Hoeesin Nikzadeh; Parisa Abdollahi; Weria Weisany; Shima Yousefi (Applied Food Research)
Due to the detrimental effects of chemical material, there is a growing interest in the use of nanomaterials as edible coatings to prolong the shelf life of meat while minimizing the potential risks to human health. Nanoencapsulation (NE) is a technique that is used to safeguard bioactive essential oils (EOs) from undesirable chemical interactions with other food components in food. In this study, we aimed to evaluate the antimicrobial activity of nanoencapsulated Mentha pulegium EOs on beef meat during storage. The experimental treatments consisted of various concentrations of pure EO at 1600 ppm and EONE at 16, 80, and 160 ppm. The meat samples were stored for 5, 10, 15, and 20 days. We evaluated different chemical parameters (pH, color, thiobarbituric acid: TBARS, and total volatile basic nitrogen: TVB-N), well as microbial parameters (the number of aerobic mesophilic bacteria count, lactic acid bacteria count, pseudomonas count, enterobacteriaceae, mold count, and yeast count). The results demonstrated that the number of bacterial counts, TBARS and TVB-N levels, and pH increased in all treatments during throughout storage. However, the increase was less pronounced in the treatments containing pure EOs and EONEs. Samples coated with EONE, particularly at a concentration of 16 ppm, exhibited the greatest effect in inhibiting most significant inhibitory effect on bacterial growth and improving enhancement of chemical parameters. Based on these findings, it can be concluded that 16 ppm EONE of M. pulegium possesses stronger antimicrobial and antioxidant properties and making it a recommended option for meat products storage.